2016
DOI: 10.1007/s00068-016-0725-y
|View full text |Cite
|
Sign up to set email alerts
|

The Gustilo–Anderson classification system as predictor of nonunion and infection in open tibia fractures

Abstract: Our study found that the Gustilo grade of open tibia fracture is by far the greatest predictor of nonunion and infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 32 publications
5
46
1
Order By: Relevance
“…This trend is further supported in the literature. A recent study created a multivariate model to evaluate the influence of several factors on infection rates and Gustilo type was found to be the greatest predictor of nonunion and infection [13] . This suggests that management of open tibia fractures should be guided by Gustilo type rather than time from injury [13] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This trend is further supported in the literature. A recent study created a multivariate model to evaluate the influence of several factors on infection rates and Gustilo type was found to be the greatest predictor of nonunion and infection [13] . This suggests that management of open tibia fractures should be guided by Gustilo type rather than time from injury [13] .…”
Section: Resultsmentioning
confidence: 99%
“…A recent study created a multivariate model to evaluate the influence of several factors on infection rates and Gustilo type was found to be the greatest predictor of nonunion and infection [13] . This suggests that management of open tibia fractures should be guided by Gustilo type rather than time from injury [13] . Our trend did not show statistical significance, possibly because the limitations of our study, which may have hidden an association between Gustilo type and infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 In the later stages, Gustilo IIIC open comminuted fractures are prone to serious complications such as limb blood supply disorders, bone nonunion and infection, and amputation. [2][3][4] The rapid development of microsurgical techniques has provided better treatment options for Gustilo IIIC open fractures. 5 Gustilo et al 3 reported that the infection rate was as high as 42% for Gustilo IIIC fractures.…”
Section: Introductionmentioning
confidence: 99%